Prevention and Control Strategies to Counter Dengue Virus Infection - Rather, Irfan A.; Parray, Hilal A.; Lone, Jameel B.; Paek, Woon K.; Lim, Jeongheui; Bajpai, Vivek K.; Park, Yong-Ha (Frontiers in Cellular and Infection Microbiology, 2017)
Dengue is currently the highest and rapidly spreading vector-borne viral disease, which can lead to mortality in its severe form. The globally endemic dengue poses as a public health and economic challenge that has been attempted to suppress though application of various prevention and control techniques. Therefore, broad spectrum techniques, that are efficient, cost-effective, and environmentally sustainable, are proposed and practiced in dengue-endemic regions. The development of vaccines and immunotherapies have introduced a new dimension for effective dengue control and prevention. Thus, the present study focuses on the preventive and control strategies that are currently employed to counter dengue. While traditional control strategies bring temporary sustainability alone, implementation of novel biotechnological interventions, such as sterile insect technique, paratransgenesis, and production of genetically modified vectors, has improved the efficacy of the traditional strategies. Although a large-scale vector control strategy can be limited, innovative vaccine candidates have provided evidence for promising dengue prevention measures. The use of tetravalent dengue vaccine (CYD-TDV) has been the most effective so far in treating dengue infections. Nonetheless, challenges and limitation hinder the progress of developing integrated intervention methods and vaccines; while the improvement in the latest techniques and vaccine formulation continues, one can hope for a future without the threat of dengue virus.